Brand management : mastering research, theory and practice - HEDING, T. (Routledge, Taylor & Francis Group, 2020)
Brand Management: Mastering Research, Theory and Practice is a valuable resource for those looking to understand how a brand can be conceptualized and thus managed in all its complexity. Going beyond the "quick fixes" of branding, it offers a comprehensive overview of brand management theories from the last 35 years. A highly regarded textbook, this fully updated third edition brings fresh perspectives on the latest research in, and analysis of, the various approaches to brand management. More than 1,000 academic sources have been carefully divided into a taxonomy with eight schools of thought - offering depth, breadth and precision to one of the most elusive management disciplines of our time. Perfectly marrying theory with practice, this comprehensive text is particularly useful for advanced undergraduate and postgraduate students of brand management, strategy and marketing"-- Provided by publisher